The Impact of Store Layout on Consumer Buying Behaviour: A Case of Convenience Stores from a Selected Township in Kwazulu Natal - Tshepo Tlapana (International Review of Management and Marketing, 2021)
The layout of a store is an important aspect influencing consumer buying behaviour and a significant determinant in the formation of a retail image. Well-designed store layouts are critical because they have a strong influence on in-store movement designs, shopping environment, shopping behaviour, and operational productivity (Behera & Mishra, 2017). When there is inconsistency in the layout of the store, some clients will abandon that establishment in search of one that delivers faster, more convenient, and better services. Taking a more thoughtful approach to retail layout can pay huge returns in terms of higher sales, customer loyalty, and, ultimately, turnover (Clark, 2003). The overarching study goal was to determine whether independent convenience stores in Kwa Mashu are aware of the effects of store layout on consumer purchasing patterns. To achieve the study's aims, a quantitative study was undertaken at Kwa Mashu convenience stores using self-administered questionnaires. A total sample of 400 respondents participated in the study. Non-probability sampling was used to select the respondents, and convenience sampling was utilized. Following that, conclusions and recommendations were derived from the literature and the study's findings. According to the findings of this survey, consumers have issues with store layout. It was discovered that the appearance of the store, merchandise display, retail atmosphere, in-store service, and accessibility are the key contributors to this pain. As a result, it is recommended that convenience shop owners in Kwa Mashu attend to the above-highlighted areas and ensure that strategies are implemented to assist customers where there is a need.